1977
DOI: 10.1093/jn/107.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Selenium, Methionine and Antioxidants against Encephalomalacia of Chicks induced by Dilauryl Succinate

Abstract: The protective effect of supplemental selenium, methionine, ascorbic acid, menaquinone and five antioxidants against encephalomalacia of chicks fed a diet containing dilauryl succinate was examined. Diauryl succinate induces vitamin E deficiency signs such as fragility of the erythrocytes and encephalomalacia. Supplementation of selenium and methionine with or without simultaneous supplementation of a low level of dl-alpha-tocopheryl acetate had little effect on preventing encephalomalacia. The preventive effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Hemolysis was completely prevented by vitamin E and partially by Se, in agreement with the report by Rotruck et al 14 ) It has been reported that Se could not prevent encephalomalacia, one of vitamin E deficiency symptoms 15 ) in chicks. Partial effect of Se on hemolysis, however, suggests that Se has a slight sparing action for vitamin E, which may be through recovering of the activity of glutathione peroxidase in plasma.…”
supporting
confidence: 90%
“…Hemolysis was completely prevented by vitamin E and partially by Se, in agreement with the report by Rotruck et al 14 ) It has been reported that Se could not prevent encephalomalacia, one of vitamin E deficiency symptoms 15 ) in chicks. Partial effect of Se on hemolysis, however, suggests that Se has a slight sparing action for vitamin E, which may be through recovering of the activity of glutathione peroxidase in plasma.…”
supporting
confidence: 90%
“…Thus, VE may have different modes of action in preventing encephalomalacia and ED, or it may play a secondary role in connection with Se in the prevention of ED. It should be emphasized that the mechanism involving VE in the protection of chicks against encephalomalacia is unknown (BARTOV and BORNSTEIN, 1980), and a Se supplement as 2 0.1 mg/kg diet has only a slight if any preventive effect against encephalomalacia (YOSHIDA and HOSHII, 1977). Another consideration, as stated by GREEN et al (1967), is that the VE requirement depends partially on the dietary content of polyunsaturated fatty acids.…”
Section: Liver Se and Non-se-glutathione Peroxidasementioning
confidence: 99%